A comparison of nutrient uptake efficiency and growth rate between different macrophyte growth forms. (15th November 2020) - Manolaki, P.; Mouridsen, M.B.; Nielsen, E.; Olesen, A.; Jensen, S.M.; Lauridsen, T.L.; Baattrup-Pedersen, A.; Sorrell, B.K.; Riis, T.
Abstract: Aquatic macrophytes grow abundantly in many lowland streams and play a key role in ecosystem functioning, such as nutrient retention. In this study, we performed a microcosm experiment to quantify and compare the contribution of two freshwater macrophyte growth forms to nutrient cycling. We measured and compared inorganic nitrogen (NH4 –N and NO3 –N) and phosphorus (PO4 –P) uptake kinetic parameters (Vmax and Cmin ) in 12 submerged and seven amphibious plant species. We tested whether relative growth rate (RGR) was related to high Vmax and low Cmin, and quantified changes in nutrient uptake kinetic in a subset of six out of 19 plants species during the growth season. Uptake rates of NH4 –N were higher in submerged compared to amphibious plants, whereas uptake rates of NO3 –N were significantly higher in amphibious species; PO4 –P uptake kinetics were not significantly different between the two growth forms. There were also significant seasonal differences in Vmax NH4 –N rate among both submerged and amphibious species and in Vmax NO3 –N among amphibious species. Highest uptake rates were observed in summer for both submerged and amphibious species. Overall, we found that nutrient uptake kinetics differed between the two growth forms within and between seasons. Consequently, the presence of both growth forms should extend the period of nutrient uptake across the year and enhance nutrient uptake within seasons. We conclude that higher functional diversity enhances annual nutrient uptake in streams and that stream restoration efforts should consider increasing the niche space available for both submerged and amphibious species. Highlights: Nutrient uptake kinetics differed significantly between plant growth forms. Higher Vmax NH4 –N for submerged and Vmax NO3 –N for amphibious species were measured. Significant seasonal differences in nutrient kinetics were also recorded. Presence of both growth forms might extend the period of uptake across the year. Higher functional diversity enhances N uptake and improves nutrient retention.